The Quality of Public Investment - Chakraborty, Shankha (IMF Working Papers; Working Paper ;, 2009)
This paper develops a growth model with specialized goods where inefficient and corrupt bureaucracies interact with the provision of public investment services in affecting the productivity of private capital, specialization, and growth. The model provides potential explanations for the contradictory empirical results on the effects of public investment found in the literature as well as for the role of the quality of public infrastructure investment in creating a gap between rich and poor countries. From a policy perspective, the paper suggests that the link between public investment and growth depends critically on the quality and efficiency of public capital.